Optimization of Reliquefaction System on Gas Carrier to Maintain The Condition and Temperature of Cargo Tank - Fitri Suprapti; Susanto Susanto; Deri Hendrawan; Retno Anggoro (Politeknik Ilmu Pelayaran Semarang, 2023)
Transport of liquefied hydrocarbon gases and their derivatives (methane, ethane, propane, butane, ethylene, propylene and other liquefied gases) is done using gas carrier tankers. Large gas carriers are equipped with re-liquefaction system to handle cargo during the process of loading, voyaging, and unloading. A reliquefaction system is installed on gas carriers to handle the Boil off-gas (BOG) problem. Operation constraints Reliquefaction system operating the reliquefaction system include the compound characteristics, liquefaction unit operating conditions, and system performance. These issues also hinder the BOG liquefaction process. This research sought to investigate the whole operation process of the system. This case study was conducted by observing the objects directly on the MT. Chinagas Legend vessel whose main cargoes are LPG. In case studies, research is carried out by studying the phenomenon of case problems that occur directly on the object. The identified problems and its resolutions could add valueable information to science. The research results revealed that MT. Chinagas Legend had a reliquefaction system with 2-stage or 3-stage options. The former type was used for butane (C4H10) cargoes and the latter was used for propane (C3H8) cargoes. The common problem in the process of reliquefaction systems was the presence of contaminants carried with seawater and clogging the filters. A leak in the intake or discharge valve slowed down the reliquefaction process and rendered it ineffective. The problems can be overcome through periodic routine inspections on components that are directly in contact with sea water, such as sea water filters.